Unanimité ou uniformité ? - Axelle Guillausseau (Mélanges de la Casa de Velázquez)
The lives of saints form the core of the Hispanic books which were so profusely disseminated beyond the Pyrenees in the second half of 16th and the first half of the 17th centuries. Based on a geographical study of some major post-Tridentine hagiographic successes dedicated to those of God’s servants engaged in Catholic reform, this article examines the circulation of these writings and the intent behind them, but it also analyses how these works were received –that is, what adaptations and appropriations were prompted by their reading in French. In fact these lives, placed at the service of Christian universalism– and particularly the spread of the Tridentine reform and the uniformisation of prayer imposed by the Bréviaire réformé– propagated models of sainthood as much as models of writing. They thus helped to achieve a profound remodelling of French hagiography in such a way as to serve in Rome the interests of the most Christian king’s subjects.